Information learning approach - Zheng, Yun (2008)
Proposed a new approach, called information learning approach, to computational learning theory. Developed an algorithm, called discrete function learning algorithm, based on information learning approach. Applied the discrete function learning algorithm to learning qualitative models of gene regulatory networks, solving classification problems, performing feature selection.